The relationship between visitor’s perception and satisfaction with quality of tourism infrastructure at Amphawa floating market - Chaiyakhet, Wachara; Thongpoon, Kumpee; Jusoh, Jamil (2016)
The Amphawa floating market is one of the famous cultural heritage destinations in Thailand that has attracted both international and domestic tourists visit as it has strongly represented the identity of their culture, architecture as well as the way of life. This paper is aimed to investigate the relationship between visitor’s perception and satisfaction with five dimensions of quality of tourism infrastructure provided at Amphawa floating market; safety, accessibility, convenient, comfortable, and services.Appropriate statistical analyses used in this research are descriptive, Pearson’s Correlation analysis and multiple regressions.The result of descriptive analysis shows that visitors’ perception of quality of tourism infrastructure was at a neutral level. However, results from a descriptive analysis prove that visitors were satisfied with the tourism infrastructure provided. Moreover, Pearson’s correlation analysis demonstrates the relationship among different variables were significant.Also, the result from multiple regression analysis shows there were two variables of visitor’s perception (safety dimension and accessibility dimension) that are significant with visitors’ satisfaction.